2021
DOI: 10.12681/jhvms.28497
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial potential of Ageratum conyzoides and its effect on Blood parameters of experimentally infected Broiler Chickens

Abstract: Coccidiosis is an infectious parasitic disease of poultry which causes heavy economic losses to commercial poultry industry. Coccidiosis has been generally controlled by using different synthetic anticoccidial drugs but, due to development of resistance to these drugs this method is losing its effectiveness. Exploration of novel and alternative compounds against avian coccidiosis is need of time now a days. In this regard, medicinal plants can serve as substitute to these synthetic anticoccidials. Thus, to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Plant extracts and essential oils have low risk of resistance development. Various plant extracts and essential oils exhibit anticoccidial activity by preventing infection or parasite dispersion (19)(20)(21)(22). PGE reduces the oocyst output of ETinfected chickens, while increasing the feed conversion ratio (FCR) and average weight, indicating the potential for coccidiosis control (23).…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts and essential oils have low risk of resistance development. Various plant extracts and essential oils exhibit anticoccidial activity by preventing infection or parasite dispersion (19)(20)(21)(22). PGE reduces the oocyst output of ETinfected chickens, while increasing the feed conversion ratio (FCR) and average weight, indicating the potential for coccidiosis control (23).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils (EOs) distilled from aromatic plants have been confirmed to provide an effect like current therapeutic approaches, and previous studies demonstrated the reversal of obesity in Wistar rats fed high carbohydrate diets [ 10 ]. EOs have many biological properties, including antioxidant activity from having redox properties, allowing them to neutralize free radicals, and anti-inflammatory, by inhibiting the release of histamine and the activation of inflammatory mediators [ 11 , 12 , 13 , 14 ]. Recently, the effects of some compounds present in medicinal plants on adipocytes have been evaluated with a favorable effect on these cells [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], adipocyte number, and oxidative stress [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these plants have been shown to have antidiabetic, antioxidant, and anti-inflammatory properties [ 3 , 6 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], including Lippia spp, which has been confirmed in previous studies to influence adipocyte functionality by decreasing lipogenesis, reversing the hypertrophic state, and generating changes in lipolysis and adipogenesis [ 33 ]. Specifically, Lippia citriodora showed an effect on some important genes in adipogenesis (CCAAT/enhancer-binding protein Alpha ( Cebpa) and Peroxisome Proliferator- activated receptor gamma ( Pparg )) and, therefore, modifies lipid accumulation, decreases adipocyte hypertrophy, and affects adipokine release after treatment for 48 h at concentrations of 50 to 400 µg/mL in 3T3-L1 adipocytes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products with antiparasitic activity could play an important role in combating these protozoan parasites. Traditional medicinal plants and their derivatives have shown favourable results against various parasitic infections [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%